2015
DOI: 10.1016/j.aquatox.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Developmental toxicity of the PBDE metabolite 6-OH-BDE-47 in zebrafish and the potential role of thyroid receptor β

Abstract: 6-hydroxy-2,2′,4,4′-tetrabromodiphenyl ether (6-OH-BDE-47) is both a polybrominated diphenyl ether (PBDE) flame retardant metabolite and a marine natural product. It has been identified both as a neurotoxicant in cell-based studies and as a developmental toxicant in zebrafish. Hydroxylated PBDE metabolites are also considered thyroid hormone disruptors due to their structural similarity to endogenous thyroid hormones. The purpose of this study was to evaluate the effects of 6-OH-BDE-47 on a developmental pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…Embryonic exposure to multiple chemicals (e.g. difenoconazole and 6-hydroxy-2, 2 0 , 4, 4 0 -tetrabromodiphenyl ether) appears to perturb the expression of thrb and results in abnormal development in zebrafish (Liang et al, 2015;Macaulay et al, 2015). These results Table S3.…”
Section: Discussionsupporting
confidence: 49%
“…Embryonic exposure to multiple chemicals (e.g. difenoconazole and 6-hydroxy-2, 2 0 , 4, 4 0 -tetrabromodiphenyl ether) appears to perturb the expression of thrb and results in abnormal development in zebrafish (Liang et al, 2015;Macaulay et al, 2015). These results Table S3.…”
Section: Discussionsupporting
confidence: 49%
“…The impact of PTU on eye development, opsin expression and pigmentation in fish has been demonstrated previously (Gan and Novales Flamarique, 2010;Macaulay et al, 2015;Raine et al, 2010). Effects of the PTUrelated compound phenylthiourea have also been reported (Bohnsack et al, 2011;Li et al, 2012), and these authors describe reduced eye size and cellular changes after treatment with this commonly used inhibitor of pigmentation in zebrafish larvae.…”
Section: Discussionmentioning
confidence: 69%
“…Recent studies revealed the adverse effect of PTU on the zebrafish thyroid system (Schmidt and Braunbeck, 2011) and embryonic development (Jomaa, 2014). Also effects of PTU on fish eye development have been reported (Macaulay et al, 2015;Raine and Hawryshyn, 2009), which makes it an interesting candidate for the current project. Due to its presence in the environment and biota (Environment Canada, 2013;Kitamura et al, 2002), TBBPA was chosen as exposure chemical in the present study as representative for a thyroid action disruptor.…”
Section: Introductionmentioning
confidence: 99%
“…From a compilation of our preliminary trial, investigations in our laboratory and selected studies from the literature (Dong et al, 2012; Dong et al, 2014; Dong et al, 2013; Holm et al., 2005; Lemly, 1997c; Macaulay et al, 2015; Villalobos et al, 2000), phenotypic responses were formulated as pre-defined categories to evaluate embryo alterations using a simple frequency analysis (presence/absence). These categories included: mortality; hatching time/success; craniofacial abnormality , change in size and/or shape of the jaw and specifically ocular deformities , agenesis, edema, asymmetry, pigment loss or irregularities; pericardial and abdominal (Pc/Ab) edema , swelling of pericardial cavity (Pc) and/or a clear space between the long axis of the body and the dorsal margin of the yolk sac (Ab); notochord malformation; spleen color , lack or change in color; gall bladder color , lack or change in color; blood pooling ; and, at or after hatch, swim bladder noninflation , partially inflated or uninflated in post-hatch individuals; other altered phenotypes, i.e.…”
Section: Methodsmentioning
confidence: 99%